Membangun Ekowisata Berbasis Perhutanan Sosial di Desa Talaga Paca, Kabupaten Halmahera Utara - Radios Simanjuntak; Novri Wangka; Eppi Manik (Universitas Lancang Kuning, 2022)
Talaga Paca Village has natural tourism potential such as lake, cave, forest and biodiversity. The existing of the natural wealth is inversely proportional to the economic welfare of the people who have a poverty rate of 75%. The community has not received the economic benefits from the beautiful nature around them. In 2019, the Ministry of Environment and Forestry gave an approval for the management of a state forest area of ​​865 ha during 35 years to Talaga Paca Village as part of the Social Forestry program. The Community Service (CS) Team of Halmahera University identified the main problem of the community was the inability to manage the tourism potential. The purpose of this CS is to implement the management of Talaga Paca ecotourism by the community so that they could receive the economic benefits for their welfare. The CS took place from April to October 2022. Through the collaboration of the parties, the CS has succeeded in improving the management of ecotourism by the community. At the moment, there have been tourist visits from within and outside the country so that the community has begun to receive economic benefits from ecotourism.